POTENSI BANGUNAN PARKIR SEBAGAI PEMBANGKIT LISTRIK TENAGA SURYA ATAP - Ari Biantara, I Gde; Satya Kumara, Nyoman; Dwi Giriantari, I. A. (Jurnal SPEKTRUM, 2022)
Solar Power Plant (PLTS) is a renewable energy that converts sunlight into electricity. However, the construction of PLTS requires a large area of land so that for urban areas it is not easy to get the required land. One of solution to this problem is to use the roof of the parking building as a rooftop solar power plant, the energy produced by the rooftop solar power plant can be exported to the network because generally the energy demand for parking buildings is not much. This paper discusses PLTS on the roof of parking buildings that have been built all over the world. The results of a review were obtained as many as 40 PLTS on the roof of the parking building which were built from 2010 to 2022 with a total capacity of 207,49 MW. This PLTS parking facility was built in the form of PLTS on the roof of the parking building, carport and parking canopy. Institutions that have built PLTS above their parking facilities include airports, banks, malls, governments, water companies, recycling companies, pharmaceutical companies, financial companies, car companies, hospitals, schools, stadiums and universities.